2017
DOI: 10.18203/2320-1770.ijrcog20173477
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of external cephalic version (ECV) in singleton pregnancy with uncomplicated breech presentation at term in a tertiary rural hospital

Abstract: INTRODUCTIONBreech presentation is the most common malpresentation. The incidence of breech presentation at term is 3-4%. Management of breech presentation at term is always being a topic of controversy. Day by day ECV is becoming a loosing Art. As delivery by Elective LSCS for Breech is associated with significantly lower neonatal mortality and morbidity, many obstetricians and pregnant women choose not to deliver breech babies vaginally. This is a significant contributing factor in increasing the caesarean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Among the neonatal outcomes, there was a slightly higher proportion of perinatal morbidity (5-minute APGAR score <7)/mortality, following unsuccessful ECV compared with successful ECV (1.4% vs 0.8%, respectively) but this difference was not significant ( Table 4 ). A similar study done in a rural tertiary care hospital in Maharashtra reported all babies to have APGAR of 9 at 5 minutes and no fetal complications or deaths attributable to ECV ( 14 ). No difference in perinatal outcome has been seen in other higher-powered studies either, rather showing comparable outcomes in both groups ( 15 ).…”
Section: Discussionmentioning
confidence: 87%
“…Among the neonatal outcomes, there was a slightly higher proportion of perinatal morbidity (5-minute APGAR score <7)/mortality, following unsuccessful ECV compared with successful ECV (1.4% vs 0.8%, respectively) but this difference was not significant ( Table 4 ). A similar study done in a rural tertiary care hospital in Maharashtra reported all babies to have APGAR of 9 at 5 minutes and no fetal complications or deaths attributable to ECV ( 14 ). No difference in perinatal outcome has been seen in other higher-powered studies either, rather showing comparable outcomes in both groups ( 15 ).…”
Section: Discussionmentioning
confidence: 87%
“…This was similar to the vaginal delivery rate reported in studies conducted by Malhi R et al (83.3%) and Vedpathak et al (88%) and significantly higher when compared to study conducted by Kathpalia et al (50%). [4][5][6] As inferred from this study; external cephalic version is an effective method in reducing the rate of cesarean delivery in cases of breech presentation. This benefit holds higher significance as it also reduces the rate of secondary cesarean delivery in future pregnancies in these women.…”
Section: Discussionmentioning
confidence: 90%
“…These findings support the hypothesis of increased success rate with parity as shown in different other studies. [4][5][6] Spontaneous reversion to breech presentation after successful ECV can occur in very few cases and only one instance was recorded in this study. Similarly, spontaneous version after failed ECV was reported in two cases after failed attempt in this study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation